Anthracycline-induced cardiac toxicity: A clinical review - Adil Abdelhameed Abbas; Aeshah Abdu Mubarak AlAzmi (Indian Journal of Medical and Paediatric Oncology)
Anthracyclines (ATCs) have a great efficacy against many types of cancer and is currently considered a cornerstone in the treatment of numerous pediatric and adult hematological and solid tumors. Great advances have been achieved after the entry of ATC group into the cancer treatment in the early 1960s, and the overall survival ratio has increased from 30% to near 70%. Due to their significant role and great value in cancer therapy, which is persistent to date, ATCs are listed in the World Health Organization model list of essential medicines. The clinical use of ATC such as doxorubicin and daunorubicin can be viewed as a sort of double-edged sword. On the one hand, ATCs play an undisputed key role in the treatment of many neoplastic diseases; on the other hand, the administration of ATC is associated with the risk of severe adverse effects. The most common side effect of the ATC group is cardiotoxicity (CTX), which may limit its use and increases mortality and morbidity rates. The clinical use of ATC is limited by unique maximum total cumulative dose (approximately 350 mg/m2) limiting CTX. ATC CTX is cumulative dose-dependent and is in most of the occasions irreversible. Lowering the cumulative dose has been proved to be useful in minimize the risk of heart failure (HF), but, yet, there is a growing concern that HF might occur following doses that were thought to be safe. The average incidence of HF is around 5% at a cumulative dose of 400 mg/m2 that becomes higher above 500 mg/m2, albeit with substantial individual variation. The newer generations ATC medications such as epirubicin, idarubicin, and mitoxantrone were thought to be safer; however, subsequent clinical studies showed more or less similar toxicity profiles. The use of cardioprotective agents (e.g., dexrazoxane and amifostine) has been associated with improved safety range; however, questions are looming on their effect on ATC antitumor effects. An overwhelming amount of clinical evidence suggests that ATCs are too good to be old. Yet, they would look much better if they caused less harm to the heart when administered as either single agents or in combination with otherwise promising new drugs. In this review article, we present a comprehensive account on the ATC and provide up to date data on their clinical use and toxicity profile. In addition, we provide a contemporary approach on the early detection, diagnosis, and treatment of ATC CTX.